Secure system with security protocol for interactions in healthcare Internet of Things - Szymoniak, Sabina (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
The Internet of Things is a network of connected devices that can communicate and share data over the Internet. These devices often have sensors that collect data for various purposes, such as usage statistics, data processing, or performing specific actions based on the collected data. Also, medical Internet of Things devices are crucial in monitoring critical functions, measuring blood glucose levels, indicating when patients require medicine, and ensuring timely medication delivery. Communication in the Internet of Things is demanding, requiring diverse protocols that address communication security concerns. These protocols must be robust and secure, considering technical factors such as the network objective, energy requirements, and the nature of the communication because they can be exploited. This paper proposes an innovative system with a security protocol that supports and improves communication security in modern Internet of Things networks. The protocol aims to enhance communication safety between interconnected devices for information exchange in medicine or healthcare, ensuring the confidentiality and integrity of sent data and devices. The proposed protocol, tested through formal and automated verification, meets all security goals, including identity verification, anonymity protection, and access revokement. It also protects against man-in-the-middle, modification, replay, and impersonation attacks.